Dynamics of Global Honey Trade: A Longitudinal Analysis from 1961 to 2022 - Pronab Jyoti Powrel; Sristi Sharma (Archives of Current Research International, 2024)
Honey is an important food on a global scale. It has deep roots in many cultures and is extensively traded worldwide. In this article we have attempted to examine global honey trade from 1961 to 2022. The purpose of this research was to understand the socio-economic, environmental and geopolitical dynamics that affect its movement from production hubs to consumer markets. This study emphasizes the complex interplay of ecological systems, technological breakthroughs, trade regulations, and consumer tastes that shape it. Accordingly, our analysis shows that honey trade has been consistently growing in all continents but with significant differences as regards the volumes and values of trade among regions. Spearman’s rho test reveals different degrees of monotonic growth trends across these regions. Further, we checked for instability across continents using core variables and performed longitudinal analysis of Trade Balance Index. Empirical evidence has been used to find out what factors could be behind changes in global honey trade dynamics. This research is intended to give valuable insights into the development processes, patterns and implications of honey trading for scholars, industry practitioners and policy makers.